PENGARUH PENGAJARAN REMEDIAL MENGGUNAKAN STRATEGI ANALOGI TERHADAP MISKONSEPSI IPA - Nur Hikmah Fitratin; Dyah Ayu Fajarianingtyas; Henny Diana Wati (Faculty of Teaching and Education, University of Wiraraja, 2018)
This research aims to find out 1) Remedial teaching implementation using analogy strategy to VII grade students of SMP Negeri 1 Saronggi, 2) Differences of IP science misconception between remedial teaching using analogy strategy and remedial teaching using direct learning strategy, 3) Improvement of student learning outcomes of grade VII after using remedial teaching using analogy strategies. This type of research is quantitative research using quasi experimental design. The sampling technique used cluster random sample technique. Technique of collecting data using test instrument with CRI and non test method. The data were analyzed using Mann-Whitney test. The results showed 1) The implementation of remedial teaching using analogy strategy of 98% with very good category and the implementation of remedial teaching using direct learning strategy of 91% with very good category. 2) Mann-Whitney test result of 0,017 indicating that there is difference of science misconception between remedial teaching using strategy analogies with remedial teaching using direct learning strategy. 3) The result of gain score in the experimental class is 0,71 with the high category, while the control class is 0,52 with the medium category. Remedial teaching using analogy strategies can be used to address misconceptions in students.